2003
DOI: 10.1021/jf025954i
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Microbial Inoculation (PseudomonasSp. Strain ADP), the Enzyme Atrazine Chlorohydrolase, and Vegetation on the Degradation of Atrazine and Metolachlor in Soil

Abstract: The concentrations of atrazine in the freshly added soils and the soils that had been incubated for 50 days significantly decreased 1 day after the addition of the enzyme atrazine chlorohydrolase or the soil bacterium Pseudomonas sp. strain ADP as compared with those in the uninoculated soils. Atrazine chlorohydrolase or ADP had no effect on the degradation of metolachlor. The half-lives of atrazine in the freshly added soils and in the aged soils after the treatment with atrazine chlorohydrolase or ADP marked… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 45 publications
(72 reference statements)
1
11
0
Order By: Relevance
“…ADP apparently had no significant effect on the dissipation of S -MET in the soil microcosms contaminated with Primextra S-Gold, suggesting that this bacterial strain is not able to degrade the chloroacetanilide herbicide, as reported by others [19]. In spite of that, the concentration of S -MET in the soils decreased moderately during the 8 days of the biodegradation experiments even though keeping values always higher than 60% of the initial concentration as described above.…”
Section: Discussionsupporting
confidence: 63%
See 2 more Smart Citations
“…ADP apparently had no significant effect on the dissipation of S -MET in the soil microcosms contaminated with Primextra S-Gold, suggesting that this bacterial strain is not able to degrade the chloroacetanilide herbicide, as reported by others [19]. In spite of that, the concentration of S -MET in the soils decreased moderately during the 8 days of the biodegradation experiments even though keeping values always higher than 60% of the initial concentration as described above.…”
Section: Discussionsupporting
confidence: 63%
“…Due to the potential effects of these substances and their metabolites for non-target aquatic organisms, risk mitigation measures are recommended particularly when the herbicidal formulation is applied in regions with vulnerable soil [31]. To date, as far as we are aware of, effective biodegradation and detoxification of MET/ S -MET or derivatives ESA and OA in soil have not been well succeeded, apparently because microorganisms do not easily metabolize their aromatic ring [1], [19], [34]. In the present work, there are evidences of the transformation of 40% initial S -MET in the contaminated soils, presumably performed by intrinsic microorganisms present in the soil, but this is not associated with an effective decontamination as discussed above.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…17,223,262,266 Strong et al 223 bioaugmented atrazine-contaminated soil with a genetically engineered E. coli strain that overproduced the atrazine chlorohydrolase enzyme responsible for dechlorinating atrazine. The researchers chemically killed the genetically engineered microorganisms (GEMs) prior to addition to a field site reducing regulatory concerns.…”
Section: Bioaugmentation With Microbial-derived Materialsmentioning
confidence: 99%
“…The survival of bioaugmentation strains is a key problem, and the persistence of Pseudomonas ADP in triazine bioremediation has previously been disputed (Morán et al, 2006;Zhao et al, 2003). Other studies using Arthrobacter different from the one used in the present study have shown that additional carbon decreases the density of the bioaugmented strain during bioremediation (Xie et al, 2012).…”
Section: Discussionmentioning
confidence: 60%